2013
DOI: 10.1016/s1470-2045(13)70464-9
|View full text |Cite|
|
Sign up to set email alerts
|

Axitinib with or without dose titration for first-line metastatic renal-cell carcinoma: a randomised double-blind phase 2 trial

Abstract: Summary Background Population pharmacokinetic data suggest axitinib plasma exposure correlates with efficacy in metastatic renal-cell carcinoma. Axitinib dose titration might optimise exposure and improve outcomes. We prospectively assessed the efficacy and safety of axitinib dose titration in previously untreated patients with metastatic renal-cell carcinoma. Methods In this randomised, double-blind, multicentre, phase 2 study, patients were enrolled from 49 hospitals and outpatient clinics in the Czech Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
146
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(153 citation statements)
references
References 33 publications
4
146
2
1
Order By: Relevance
“…Another prospective, multicenter phase II study is being conducted in Canada, which looks at the potential of dose escalation beyond 50 mg/day in patients who are able to tolerate the drug, and schedule adjustment before dose reduction in those who experience treatment-related toxicity (NCT01499121) [17]. In a phase II trial evaluating dose titration of axitinib, the majority of the patients who underwent dose titration received a greater ORR, although no PFS benefit was seen, thereby keeping the question of benefit to dose escalation open at this time [20]. Trials that explore individual dose escalation for patients on sunitinib will yield further insights on maximizing objective response and duration of PFS in mRCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another prospective, multicenter phase II study is being conducted in Canada, which looks at the potential of dose escalation beyond 50 mg/day in patients who are able to tolerate the drug, and schedule adjustment before dose reduction in those who experience treatment-related toxicity (NCT01499121) [17]. In a phase II trial evaluating dose titration of axitinib, the majority of the patients who underwent dose titration received a greater ORR, although no PFS benefit was seen, thereby keeping the question of benefit to dose escalation open at this time [20]. Trials that explore individual dose escalation for patients on sunitinib will yield further insights on maximizing objective response and duration of PFS in mRCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 122 RCC patients were randomized to either axitinib or placebo dose titration. The axitinib dose titration group showed an increased ORR compared to the placebo group ( P = 0.019)43, but this did not result in improved OS ( P = 0.162) 44. One small study ( n = 24) also found a relationship between axitinib C min >5 ng/mL and tumor response and the occurrence of hypertension, hyperthyroidism, and proteinuria 45.…”
Section: Practical Recommendations For Tdm Of Kis In Oncologymentioning
confidence: 93%
“…Diastolic blood pressure (dBP) ≥90 mmHg has been associated with increased probability of response, PFS, and OS in RCC patients 41, 42. Based on these results, a randomized phase II trial to individualize axitinib dose based on dBP has been performed 43. In total, 122 RCC patients were randomized to either axitinib or placebo dose titration.…”
Section: Practical Recommendations For Tdm Of Kis In Oncologymentioning
confidence: 99%
“…Treatment-naïve patients with mRCC received axitinib 5 mg b.i.d. (Figure 3 [8,9] [9]. In the nonrandomized group, 54 (59%; 95% CI: 49-70) patients had an OR, suggesting that patient selection criteria based on tolerability correctly indicated which patients had adequate axitinib exposure levels at 5 mg b.i.d.…”
Section: Interpatient Variability In Drug Exposure Translates Into Vamentioning
confidence: 99%
“…Because of the interpatient variability in half-life and exposure seen with axitinib, it is not possible to predict the exact exposure level a patient will have. However, Rini et al demonstrated that increasing the axitinib dose leads to increased exposure [9]. Patients who, based on tolerability criteria, were eligible for subsequent dose escalation up to 7 mg b.i.d.…”
Section: Interpatient Variability In Axitinib Exposurementioning
confidence: 99%